2005
DOI: 10.1093/carcin/bgi232
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of DNA repair genes and risk of non-small cell lung cancer

Abstract: Lung cancer is a leading cause of cancer mortality with an inter-individual difference in susceptibility to the disease. The inheritance of low-efficiency genotypes involved in DNA repair and replication may contribute to the difference in susceptibility. We investigated 44 single nucleotide polymorphisms (SNPs) in 20 DNA repair genes including nucleotide excision repair (NER) genes XPA, ERCC1, ERCC2/XPD, ERCC4/XPF and ERCC5/XPG; base excision repair (BER) genes APE1/APEX, OGG1, MPG, XRCC1, PCNA, POLB, POLiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
280
4
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(324 citation statements)
references
References 51 publications
25
280
4
13
Order By: Relevance
“…The results of studies on XPF and ERCC1 variants and the risk of cancer are also contradictory. [29][30][31]. The XPG gene encodes the 3' endonuclease of the NER pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies on XPF and ERCC1 variants and the risk of cancer are also contradictory. [29][30][31]. The XPG gene encodes the 3' endonuclease of the NER pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The NBS1 (Nibrin) protein is a component of the MRN-complex, which recognizes DSBs [31]. Most studies investigating the NBS1 Glu185Gln polymorphism have focused on assessing the risk of breast cancer [32].…”
Section: Introductionmentioning
confidence: 99%
“…5 To date, a number of molecular epidemiological studies have been done to evaluate the association between XPA À4G>A polymorphism and different types of cancer risk in diverse populations. The tumor types included lung cancer, 6,13,22,24,[29][30][31][32][33][34] gastric cancer, 7,17 colorectal cancer, 8,12,23 squamous cell carcinoma of the head and neck, 8,10 basal and squamous cell carcinomas of the skin (BCC and SCC), 20,27 breast cancer, 8,18,26 esophageal cancer, 11,14,15 and so on. However, the results were inconsistent or even contradictory.…”
mentioning
confidence: 99%
“…PCNA is reported to be overexpressed in cancer cells and it is also very often used as a marker of proliferation [12]. In the base excision repair pathway, PCNA (A1876G) polymorphisms were found to be associated with increased risk of non-small cell lung cancer [13]. It is reported that two mutant forms of PCNA formed due to amino acid substitutions cause defects in mismatch repair system.…”
Section: Introductionmentioning
confidence: 99%